190k views
2 votes
Translate the graph according to the rule (x, y) → (x + 2, y).

The first graph goes with the question.

Translate the graph according to the rule (x, y) → (x + 2, y). The first graph goes-example-1

1 Answer

2 votes

(x, y) → (x, y + n) - translate the graph n units up

(x, y) → (x, y - n) - translate the graph n units down

(x, y) → (x - n, y) - translate the graph n units left

(x, y) → (x + n, y) - translate the graph n units right

---------------------------------------------------------------------------

(x, y) → (x + 2, y)

translate the graph 2 units right.

Translate the graph according to the rule (x, y) → (x + 2, y). The first graph goes-example-1
User Lukmo
by
5.4k points